Pemilihan Tempat Bertelur Nyamuk Aedes aegypti pada Air Limbah Rumah Tangga di Laboratorium - I Made Sudarmaja; SugengO Juwono Mardihusodo (Jurnal Veteriner, 2009)
A laboratory experimental study was conducted to observe the types of household waste water aspreferential sites for Aedes aegypti to lay their eggs. In this study, three types of waste water were used i.e.soap contaminated water, detergent contaminated water and tap water respectively. The results of thestudy showed that soap contaminated water (0,5 gram/liter) and tap water were preferential sites forAedes aegypti to lay their eggs, while detergent contaminated water was not. The number of mosquito eggsfound in soap contaminated water was not significantly different with those found in tap water but both ofthem were significantly higher than those found in detergent contaminated water.